Draw a Pedigree During the Neurological Consultation. Issue 1 (1st February 2005) - Razvi, Saif S.M.; Bone, Ian
Abstract : INTRODUCTION Inherited genetic disorders account for about 5% of all medical consultations. The importance of a genetic contribution to a widening spectrum of disorders is becoming evident in neurology, indeed in all facets of medicine. Genetic factors may contribute to the development of disease, influence its course and severity, prognosis and response to therapy. Therefore, as our knowledge of the human genome expands, efforts are being made to identify genetic predispositions and influences to improve identification of risk, target pharmacotherapy, design gene therapy, and to provide more accurate assessment of prognosis. Recognition of risk should facilitate timely screening and early or presymptomatic treatment when available; and even in the absence of accepted treatment strategies this may still encourage appropriate lifestyle measures to reduce risk. Better assessment of genetic risk is therefore an essential part of modern clinical assessment in all patients. A comprehensive family history is the first step and